Tolerance in Multireligious Schools: Practices and Challenges - Lutfatulatifah, Lutfatulatifah; Ramdaeni, Suci (AWLADY : Jurnal Pendidikan Anak, 2024)
This research aims to explain the practice of religious tolerance in early childhood education in Cirebon, Indonesia. Cirebon has a strong Islamic religious background, but is also diverse in terms of ethnicity, race, culture and religion. With a semi-ethnographic approach, this research was conducted in a Buddhist-based kindergarten which has religious diversity among its students. The research results show that there is ambivalence in the application of religious values, where the Puja Bakti ritual is considered as a way to teach moral values and goodness, but is also taught as a form of worship. Economic constraints are an important factor limiting schools' ability to provide appropriate religious education for all students. This research emphasizes the importance of inclusive and sensitive approaches to religious diversity in early childhood education, as well as greater financial support to create educational environments that respect all faiths.